2018
DOI: 10.1136/archdischild-2018-315565
|View full text |Cite
|
Sign up to set email alerts
|

Causes and characteristics of injury in paediatric major trauma and trends over time

Abstract: ObjectiveTo investigate causes, characteristics and temporal trends of paediatric major trauma.DesignA retrospective review of paediatric major trauma (<16 years of age) was conducted using data from the population-based Victorian State Trauma Registry from 2006 to 2016. Temporal trends in population-based incidence rates were evaluated using Poisson regression.SettingVictoria, Australia.ResultsOf the 1511 paediatric major trauma patients, most were male (68%), had sustained blunt trauma (87%) and had injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 24 publications
7
39
3
Order By: Relevance
“…In the United States, where trauma reporting processes have been more stable, an 8.3% reduction in injury-related presentations was noted between 2006 and 2012 14. Similarly, there has been no increase in reported paediatric major trauma in recently reported data from Australia 15…”
Section: ​Discussionmentioning
confidence: 98%
“…In the United States, where trauma reporting processes have been more stable, an 8.3% reduction in injury-related presentations was noted between 2006 and 2012 14. Similarly, there has been no increase in reported paediatric major trauma in recently reported data from Australia 15…”
Section: ​Discussionmentioning
confidence: 98%
“…Data from 103 German trauma centres also revealed that most common causes of injury in children were traffic related accidents, followed by falls (Buschmann et al, 2008). Study from 1511 Australian children also showed that motor vehicle collisions were the commonest cause of injury, followed by "struck by/ collisions with an object or person" (Beck et al, 2018). On the other hand, a study from Varanasi, in one of the largest trauma centres in India, reported falls to be the commonest cause of injury among children (Kunwar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, we excluded patients who were admitted directly in the neurosurgery and orthopaedic departments. Data from the German and the Australian cohort showed that head injuries were most common among children (Buschmann et al, 2008;Beck et al, 2018). Data from the "Trauma Audit and Research Network" in UK showed that limb injuries were commonest among 24,218 paediatric trauma cases (Bayreuther et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Year of injury, demographics, injury event details, injury diagnoses, injury severity, and other relevant factors were extracted from the VSTR. Demographic data included sex (male, female) and age in years at the time of injury, categorised into four groups [23]: <1 year, 1-5 years, 6-10 years, and 11-15 years. The Australia Bureau of Statistics (ABS) Socio-Economic Indexes for Areas (SEIFA) were accessed, with the Accessibility/Remoteness Index of Australia (ARIA) (0 = regional, 1 = major city) and the quintiles for the Index of Relative Socioeconomic Advantage and Disadvantage (IRSAD) (low score = greater disadvantage, high score = greater advantage) were included as indicative measures of socioeconomic status and geographic remoteness.…”
Section: Methodsmentioning
confidence: 99%